2021
DOI: 10.6007/ijarbss/v11-i9/11120
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Competency-Based Succession Planning at Higher Education Institution in Malaysia

Abstract: This conceptual paper highlights the necessity to have a proper workforce and succession planning in place in order to have the right leadership in the right place at the right time. Leaders who are incompetent or exhausted may impose adverse impacts on the effectiveness of succession planning. Nowadays, leaders face complex challenges than those in the past with increasing workloads and responsibilities to ensure that organisational agendas are sustained. Competent and skilled leaders are needed to carry out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
0
1
Order By: Relevance
“…The findings of the third hypothesis stated that succession planning information significantly influences employees' behavioural outcomes, which means that respondents of the selected manufacturing firms established adequate information for succession trajectories and career growth. This is contrary to the findings of [ 37 ] who suggested that leaders who are inept or fatigued may have a negative influence on succession planning's efficacy. As a result, an organisation should be proactive in its succession planning and strategize for future performance and sustainable employees' behavioural outcomes.…”
Section: Summary Of Findingscontrasting
confidence: 99%
“…The findings of the third hypothesis stated that succession planning information significantly influences employees' behavioural outcomes, which means that respondents of the selected manufacturing firms established adequate information for succession trajectories and career growth. This is contrary to the findings of [ 37 ] who suggested that leaders who are inept or fatigued may have a negative influence on succession planning's efficacy. As a result, an organisation should be proactive in its succession planning and strategize for future performance and sustainable employees' behavioural outcomes.…”
Section: Summary Of Findingscontrasting
confidence: 99%
“…AVE can be used to measure the reliability of latent variable component scores, and the results are more conservative than composite reliability. It is recommended that the AVE limit value be greater than 0.50, while for composite reliability it is 0.7 (Ghazali et al, 2023). The AVE values calculated in this study are as follows: Discriminant validity is used to ensure that the concept of each construct or latent variable is different from the other variables.…”
Section: Demographic Characteristics Of Respondentsmentioning
confidence: 99%
“…Previous studies have addressed the impact of succession planning on business persistence (Ogbari et al, 2015), the effect of succession planning on employee engagement (Gulzar & Durrani, 2014), and the impact of succession planning practices on the performance of nongovernmental organizations (NGOs) (Maguta, 2016). In Malaysia, the importance of succession planning is highlighted in the context of family businesses (Lim, 2019; "Succession planning is key," 2021), Small and Medium Enterprises (SMEs) (Ndubisi, 2010;Mokhber et al, 2017) as well as the education sector (Chia et al, 2021;Ghazali et al, 2021). However, it was identified that there is an apparent knowledge gap and lack of research on the effectiveness of types of succession planning in the HRM field and the context of social enterprises.…”
Section: Research Problemmentioning
confidence: 99%